2011
DOI: 10.1111/j.1540-8183.2011.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Stent Thrombosis Risk with the XIENCE V® Everolimus-Eluting Coronary Stent: Evidence from Randomized and Single-Arm Clinical Trials

Abstract: The XIENCE V® Everolimus-Eluting Coronary Stent System (EECSS) has been evaluated in multiple randomized controlled trials (RCTs) with several different comparators (SPIRIT FIRST, SPIRIT II, SPIRIT III, SPIRIT IV, COMPARE, ISAR-TEST 4, SORT-OUT IV, and RESOLUTE All-Comers RCT). The available results consistently demonstrated numerically low stent thrombosis (ST) rates in the XIENCE V arm treated patients. The use of XIENCE V in complex patients with diabetes, overlapping stents, multistenting, and other known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Other patient specific characteristics may contribute, such as patient co-morbidities (diabetes, renal failure and acute MI) and lesion characteristics. Compliance to DAPT and platelet responsiveness also plays a role in ST rates observed in DES (Bezenek et al, 2011). Procedural factors related to smaller luminal dimensions, such as stent under-expansion or malapposition are risk factors for ST, in addition to stent length, multi-stenting, persistent slow flow, positive remodeling, dissections, geographic miss, residual stenosis, and late stent malapposition which have all been related to ST (Bezenek et al, 2011).…”
Section: Current Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…Other patient specific characteristics may contribute, such as patient co-morbidities (diabetes, renal failure and acute MI) and lesion characteristics. Compliance to DAPT and platelet responsiveness also plays a role in ST rates observed in DES (Bezenek et al, 2011). Procedural factors related to smaller luminal dimensions, such as stent under-expansion or malapposition are risk factors for ST, in addition to stent length, multi-stenting, persistent slow flow, positive remodeling, dissections, geographic miss, residual stenosis, and late stent malapposition which have all been related to ST (Bezenek et al, 2011).…”
Section: Current Challengesmentioning
confidence: 99%
“…Despite these challenges however, few DES have emerged as demonstrating a consistent numerically low rate of ST across clinical trials. The XIENCE V and XIENCE PRIME DES remain two of the DES with the lowest ST event profile across RCT, single-arm, and all-comer trials, despite reduced DAPT compliance observed at 2 years in the COMPARE all-comers trial; the combination of stent design, thin struts, bio-compatible polymer coating technologies, and drug may contribute to numerically low ST rates consistently observed (Bezenek et al, 2011).…”
Section: Current Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of the inclusion stent scaffolds were available in diameters of 2.5, 3.0, and 3.5 mm, and lengths of 18, 23, and 28 mm. If an additional DES was required, it was a Xience Pro ® stent (Abbott Vascular) [5,6].…”
Section: Study Devicementioning
confidence: 99%